Two-dimensional resistive MHD simulation of the optimized plasma formation in the spherical tokamaks. (21st April 2021) - Ahmadi, T.; Tanabe, H.; Ono, Y.
Abstract: We present 2D global MHD simulation results of the optimized start-up scenarios for the spherical tokamak to maximize the ion heating energy determined by the value of the poloidal private flux during the merging start-ups. The series of simulations has successfully revealed the dependence of the poloidal private flux on the in-vessel poloidal coils' separation length under the fixed amount of coils' magnetic energy. The radial and azimuthal locations of the internal coils need to be optimized to maximize high private flux and consequently high ion heating energy. In the case of a two poloidal field (PF) coils system, the private flux and ion heating energy increase with the coils' separation length. Installing two additional PF coils improves the private flux significantly, even if the coils' separation length is short.